THE EFFECT OF VARIATIONS OF COMPOSITION OF FELSDPAR AND THE SHELL OF PENSI SHELL (Corbicula Moltkiana) FROM LAKE MANINJAU ON THE FLEXIBILITY OF DENTURE - Arni Sopianti; Riri Jonuarti; - Ratnawulan; - Gusnedi (Department of Physics – Universitas Negeri Padang UNP, 2021)
Utilization of waste pensi shells (Corbicula Moltkiana) in Lake Maninjau has not been fully optimal so that a more economical business is needed. One of them is the use of calcium oxide in pensi shells. Calcium oxide is one of the most commonly used calcium in the manufacture of dentures. This study aims to determine the value of the optimum flexural strength of the denture in order to obtain a higher quality denture material on the pensi shell that can be utilized and which has economic value. The method used is the experimental method. The sample used in this study with a size of 90 mm X 18 mm X 8 mm for testing flexibility / flexural strength. The total samples used in this study were 12 samples for testing the flexibility/flexural strength using a bending testing machine. For the use of pensi shell material, a calcination process was carried out at a temperature of 1000℃ on the pensi shell material and then characterized using XRF to determine the ingredients. The results of the characterization using XRF showed that pensi shells contain calcium elements of 97.121% and about 3% other elements such as Si, Al, P, Ag, Mn and Fe. Then the pensi shell material is mixed with other ingredients such as felsdpar, quartz, and kaolin. The material is mixed and then molded for flexural testing specimens. Based on the test results of this study, the highest flexibility value for denture samples was found in sample 4 with the most variations of pensi shell powder. The highest denture flexibility value is 25.778 MPa with a variation of 30 gram pensi shell powder in sample 4. The lowest denture flexibility value is 5.727 MPa with a variation of 0 gram pensi shell powder in sample 1. This is due to the addition of pensi shell powder. can increase the value of flexibility in dentures. The increase in the flexibility value was influenced by the CaO content obtained from the pensi shell powder.